Feasibility of an Extensive Strategy for Adult Diagnosis of Attention Deficit Hyperactivity Disorder Among Patients Suffering From Substance Use Disorders - Therribout, Norman; Karsinti, Emily; Morel, Alix; Dereux, Alexandra; Vorspan, Florence; Romo, Lucia; Icick, Romain (Frontiers in Psychiatry, 2022)
INTRODUCTION: Attention Deficit Hyperactivity Disorder (ADHD) is found in up to 20% adults with Substance Use Disorder (SUD). ADHD + SUD is associated with a more complex clinical presentation and poorer outcomes than each disorder alone. In the presence of SUD, adult ADHD may be even more difficult to diagnose as both disorders can mimic or hide the symptoms of each other. Our university hospital in Paris recently started an extensive outpatient diagnostic procedure for adult patients with SUDs to ascertain or refute ADHD diagnosis and to provide therapeutic guidance. Here, we report the acceptability of the assessment procedure for patients and preliminary description of the current and lifetime clinical profiles as a function of the diagnostic conclusion “ADHD vs. no ADHD”. METHOD: Adult ADHD suspected SUD patients were included in the current pilot study after stating they had no objection that their de-identified data were used for research purposes, according to French ethical procedures. Patients were evaluated for ADHD, comorbid mental disorders, cognitive state and dimensional psychological variables. They were assessed by trained psychologists and psychiatrists using standardized tools over a day. RESULTS: Out of 18 eligible patients, 17 were included in the cohort (1 excluded) and none refused to participate in the research protocol. Thirteen (76%) participants were diagnosed with ADHD according to the DIVA-5. All patients appointed for the ADHD diagnostic procedure came, respected schedules and finished the evaluation. All patients were impaired on cognitive functioning and were highly comorbid, but ADHD patients seems to suffer even more from those conditions, especially for cannabis and stimulant use disorders. DISCUSSION: Preliminary results show high acceptability of the procedure by ADHD-SUD patients. This result could be explained by all the organization adapted to the psychopathology. Patients’ baseline motivation to participate also represents an uncontrolled variable that could promote the ability to follow the procedure. Acceptance results of the protocol are promising and represent a starting point to identify the best procedures to design patient-centered pharmacological and non-pharmacological therapies.